Low-modulus anti-fatigue composite hydrogel as well as preparation method and application thereof

By combining low-modulus hydrogel with stretchable fabrics woven by high-strength fibers, and regulating interface performance through freeze-thaw cycle and annealing and drying processes, the problem of insufficient fatigue resistance in low-modulus applications is solved, and composite hydrogels with low-modulus and high fatigue threshold are achieved, which are suitable for applications in high-circumference fatigue environments.

CN119526843AActive Publication Date: 2025-02-28XI AN JIAOTONG UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411791153.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Existing high-toughness hydrogels are prone to fatigue damage under long-term cyclic loading conditions, and the introduction of high-content hard phases to increase the fatigue threshold will lead to an increase in modulus, making it difficult to meet the needs of low-modulus applications.

Method used

The stretchable fabric woven with a low-modulus hydrogel and a high-strength fiber with a curved fiber structure is combined with a stretchable fabric braid. The interface performance between the fabric and the hydrogel matrix is ​​regulated through freeze-thaw cycle and annealing and drying processes, forming a strong interface for coordinated deformation and improving fatigue resistance.

Benefits of technology

A composite hydrogel with low modulus (less than 1MPa) and high fatigue threshold value (greater than 5000J/m2) is achieved, with a fatigue threshold value higher than that of traditional hydrogels with the same modulus and remain intact in high-period fatigue tests. It is suitable for applications such as artificial heart valve prosthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119526843A_ABST
    Figure CN119526843A_ABST
Patent Text Reader

Abstract

The invention discloses low-modulus anti-fatigue composite hydrogel as well as a preparation method and application thereof. According to the composite hydrogel, low-modulus hydrogel is used as a soft matrix layer, and stretchable fabric is used as a reinforced knitted fabric layer; the preparation method comprises the following steps: putting the stretchable fabric into a hydrogel pre-polymerization solution, and forming a three-dimensional polymer network through a circulating freeze-thaw treatment method. And then putting the hydrogel into a drying oven, and carrying out drying and annealing treatment to form the annealed composite hydrogel. And finally, immersing the annealed composite hydrogel in deionized water until the composite hydrogel is completely swelled to form the required composite hydrogel. The invention also discloses application of the composite hydrogel as an artificial heart valve prosthesis. The composite hydrogel has the advantages of biological tissue-like stress-strain behavior, low modulus, high fatigue threshold value and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer hydrogels, in particular to a low modulus anti-fatigue composite hydrogel, a preparation method and application thereof. Background Art

[0002] Hydrogel is a high molecular polymer material containing a large number of water molecules. Hydrogel has good stretchability and biocompatibility. In recent years, it has been widely used in many fields such as flexible sensors, soft robots, bioadhesives, wearable devices, artificial tissues, etc. The further development of smart medical care, flexible electronics, and robotics industries is inseparable from the development of high-performance hydrogels. The broad prospects of hydrogels in these fields have made the research on high-performance hydrogels one of the hot research directions in multidisciplinary fields such as materials, mechanics, and biomedicine.

[0003] Although researchers have developed a number of highly tough and stretchable hydrogels, hydrogels are still challenging in practical application environments. For example, even if the hydrogel has high toughness, it is prone to fatigue failure under long-term cyclic loading service conditions. In recent years, researchers have also proposed some anti-fatigue hydrogel strategies, such as annealing and drying, ice template assisted salting out hydrogels, fiber composite hydrogels, phase separation hydrogels, etc. These hydrogels disperse the stress concentration at the crack tip by introducing hard phase crystallization, hard phase fibers, hard phase separation, etc., so that the fatigue threshold of the hydrogel is increased. However, the introduction of this type of high-content hard phase will increase the modulus of the hydrogel, which is not applicable in application scenarios that require low modulus. Therefore, how to obtain an anti-fatigue hydrogel with a low modulus is still a problem that needs to be solved urgently. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a low modulus anti-fatigue composite hydrogel to solve the problem that the modulus of the hydrogel will be increased simultaneously when the reinforcing phase is used in the past. Another technical problem that the present invention is to solve is to provide a method for preparing a low modulus anti-fatigue composite hydrogel, which can regulate the interface between the fabric and the hydrogel matrix so that a strong interface is formed between the fabric and the hydrogel, thereby synergistically deforming to achieve the composite hydrogel having the characteristics of low modulus and high fatigue threshold after swelling equilibrium. Another technical problem that the present invention is to solve is to provide the application of the above-mentioned composite hydrogel that can achieve low modulus and anti-fatigue.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A low modulus fatigue-resistant composite hydrogel comprises a hydrogel-based soft matrix layer and a reinforced knitted fabric layer covering the hydrogel-based soft matrix layer; the material of the hydrogel-based soft matrix layer is a low modulus hydrogel; the material of the reinforced knitted fabric layer is a stretchable fabric woven from high-strength fibers with a curved fiber structure, which can form bridging fibers under cyclic loads to resist fatigue crack propagation.

[0007] The modulus of the hydrogel-based soft matrix layer is less than 1Mpa, and the stretch ratio is greater than 2; the strength of the reinforced knitted fabric layer is greater than 10MPa, and the gram weight is greater than 80g / cm 2 , the underfill coefficient is greater than 10; the soft matrix-knitted fabric forms a strong interface, which makes the soft matrix-knitted fabric deform synergistically, effectively improving the fatigue resistance of the hydrogel, and the fatigue threshold value of the composite hydrogel is greater than 5000J / m 2 At the same time, the initial modulus of the knitted fabric is low, so that the composite hydrogel maintains a low modulus of less than 1MPa.

[0008] The method for preparing the low modulus fatigue-resistant composite hydrogel comprises the following steps:

[0009] (1) Laying a single layer or multiple layers of stretchable fabric in a mold;

[0010] (2) pouring a hydrogel precursor solution into the mold of step (1), subjecting the entire mold to a freeze-thaw cycle, and demolding the mold to form a prefabricated composite hydrogel;

[0011] (3) placing the prefabricated composite hydrogel obtained in step (2) in an oven for annealing and drying to obtain an annealed composite hydrogel;

[0012] (4) Immersing the annealed composite hydrogel obtained in step (3) in a solution until complete swelling equilibrium is reached; and obtaining a low modulus fatigue-resistant composite hydrogel.

[0013] The mold in step (1) includes two glass plates and a layer of hollow silicone pad, wherein the hollow silicone pad is located between the two glass plates.

[0014] The fibers used for the stretchable fabric in step (1) include any one or more of metal, polyurethane, nylon, Kevlar, polyester, polytetrafluoroethylene, ultra-high molecular weight polyethylene, polyetheretherketone, polysulfone, polyether, polyamide, and polyetherimide; the stretchable fabric structure is any one or more of warp knitting or weft knitting plain needle structure, rib structure, double rib structure, and double-sided structure; the diameter of any fiber in the stretchable fabric in step (1) is 10 to 100 microns; the laying angle θ between the multiple layers of stretchable fabric laid in the mold in step (1) is 1-360°; the stretchable fabric can be pre-stretched and tensioned with a deformation of up to 200%.

[0015] The precursor in the hydrogel precursor solution of step (2) includes any one or a combination of at least two of compounds selected from the group consisting of polyvinyl alcohol, polyethylene glycol, acrylamide, acrylic acid, hyaluronic acid, cellulose, sodium alginate, chitosan, etc.; the solvent of the hydrogel precursor solution is any one or more of water, tetrahydrofuran, dimethyl sulfoxide, ethanol, and acetone; and the mass percentage of the precursor in the precursor solution is 1 to 20%.

[0016] The temperature of the cold source used in the freeze-thaw cycle of step (2) is -80 to -20°C; the freezing time is 6 to 24 hours.

[0017] The temperature control of the annealing and drying in step (3) is 30-110° C., and the temperature control time is 1-1440 min.

[0018] The swelling solution in step (4) is any one of deionized water, dimethyl sulfoxide, ethanol, and ionic liquid, or a combination of at least two of them. The swelling time is 1 to 2880 minutes, and the temperature of the immersion in the solution is 0 to 80°C.

[0019] The application of the low modulus fatigue-resistant composite hydrogel is to cut the composite hydrogel into artificial heart valve leaflets, sew them on a metal stent, and assemble them into an artificial heart valve prosthesis. Under the action of pulsating flow, the artificial heart valve prosthesis can open and close smoothly and withstand 25,000,000 cyclic loads without being damaged.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) A low modulus anti-fatigue composite hydrogel of the present invention has a low modulus (<1MPa) and a high fatigue threshold (>5000J / m 2 ), the fatigue threshold is higher than that of previous hydrogels with the same modulus;

[0022] (2) The method for preparing the low modulus fatigue-resistant composite hydrogel of the present invention adopts an annealing and drying process to regulate the interface properties of the fiber and the matrix, so that the prepared hydrogel has a strong interface and anti-swelling properties, and the soft matrix-knitted fabric can be deformed synergistically. The method of the present invention is simple and effective, and solves the problem of interface failure under swelling of traditional composite hydrogels.

[0023] (3) The composite hydrogel is prepared into an artificial heart valve prosthesis, which can open and close well and pass the high-cycle fatigue life of more than 25,000,000 times, which is unattainable under the existing hydrogel high-cycle fatigue test. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the mold in Example 1.

[0025] Figure 2 Schematic diagram of the laying angle of multiple layers of fabric in Example 6.

[0026] Figure 3 This is a macroscopic morphology of the composite hydrogel in Example 1.

[0027] Figure 4 This is a microscopic morphology of the composite hydrogel in Example 1.

[0028] Figure 5 This is a uniaxial tensile strain-stress curve of the composite hydrogel in Example 1.

[0029] Figure 6 This is a strain-stress curve diagram of the fracture toughness measurement of the composite hydrogel in Example 1.

[0030] Figure 7 This is a graph of fatigue threshold values ​​of the composite hydrogel in Example 1.

[0031] Figure 8 This is a uniaxial tensile strain-stress curve of the composite hydrogel in Example 2.

[0032] Fig. 9 This is a strain-stress curve diagram of the fracture toughness measurement of the composite hydrogel in Example 2.

[0033] Fig.10 This is a graph of fatigue threshold values ​​of the composite hydrogel in Example 2.

[0034] Fig.11 This is a picture of the artificial heart valve prosthesis prepared from the composite hydrogel in Example 2.

[0035] Fig.12 This is a diagram showing the opening and closing states of the artificial heart valve prosthesis prepared from the composite hydrogel in Example 2.

[0036] Fig.13 This is a morphology picture of the artificial heart valve prosthesis prepared from the composite hydrogel in Example 2 after high cycle fatigue testing. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings. The following examples are only for illustrating the present invention and do not limit the protection scope of the present invention.

[0038] Example 1: Preparation method of a low modulus anti-fatigue composite hydrogel 1

[0039] First, a mold made of two glass plates and a 0.2mm hollow silicone pad was prepared; a piece of 0.15mm thick plain weave fabric was soaked in a mixed solution containing 90wt% alcohol and 10wt% acetone overnight to remove oil and wax on the surface of the fabric, and then placed in the mold. A 10% mass fraction of polyvinyl alcohol aqueous solution was poured into the mold containing the fabric. The mixture and the mold were placed in a refrigerator, frozen at -20℃ for 12 hours, and then thawed at room temperature for 3 hours. Next, the composite hydrogel in the mold was removed and annealed in a constant temperature box at 40℃ for 2 hours. Finally, the annealed composite material was soaked in deionized water for 24 hours.

[0040] The macroscopic morphology of the fabric provided in Example 1 was characterized by an optical microscope. Figure 3 As shown. Figure 3 It can be seen that it has two main directions.

[0041] The microscopic morphology of the cross section of the composite hydrogel prepared in Example 1 was characterized by scanning electron microscopy. Figure 4 As shown. Figure 4 It can be seen that the interface between the two is good.

[0042] The composite hydrogel prepared in Example 1 was subjected to tensile mechanical testing using an electronic universal testing machine. The strain-stress curve is shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the composite hydrogel has a J-type stress-strain curve and anisotropy similar to biological tissues. The test conditions of the electronic universal testing machine are: at room temperature, the mechanical sensor is 100N, and the stretching speed is 50mm / min.

[0043] The composite hydrogel prepared in Example 1 was tested for fracture toughness using an electronic universal testing machine. The stress-strain curve is shown in the figure below: Figure 6 As shown by Figure 6 It can be seen that the fracture toughness of the composite hydrogel along the latitudinal loading is 53 kJ / m 2 The fracture toughness along the longitudinal direction is 52 kJ / m 2 . Among them, the test conditions of the electronic universal testing machine are: at room temperature, the mechanical sensor is 100N, and the tensile speed is 50mm / min. The method of fracture toughness test is: cut the test sample into a rectangle with a width of 50mm and a height of 30mm. For specimens with prefabricated cracks, introduce a 20mm pre-crack in the middle plane. Fix the edge of the specimen on the acrylic plate to ensure that the gauge height is 10mm. Measure the thickness of each specimen with a micrometer screw before the test. According to the specimen with prefabricated cracks, the critical fracture tensile ratio λc is determined at the starting point of crack extension. The calculation method of fracture toughness G is as follows, Γ=W(λc)×H,

[0044] Where W(λc) is the integral area of ​​the stress-strain curve of the notched specimen from 1 to the critical fracture tensile ratio. H is the initial gauge height of the specimen.

[0045] The fatigue resistance of the composite hydrogel provided in Example 1 was tested along two main directions using an electronic universal testing machine. The test results are as follows: Figure 7 As shown by Figure 7 It can be seen that the fatigue threshold value of the composite hydrogel along the latitudinal loading is 5173 J / m 2 The fatigue threshold value along the longitudinal direction is 4880J / m 2 . Among them, the test conditions of the electronic universal testing machine are: at room temperature, the mechanical sensor is 100N, and the tensile speed is 50mm / min. The method of fatigue threshold value test is: cut the test sample into a rectangle with a width of 50mm and a height of 30mm. For specimens with prefabricated cracks, introduce a 20mm pre-crack in the middle plane. Fix the edge of the specimen on the acrylic plate to ensure that the gauge height is 10mm. Measure the thickness of each specimen with a micrometer screw before the test. The specimen was immersed in a deionized water environment for testing. During the test, the unnotched specimens and the specimens with prefabricated cracks were subjected to cyclic loading with a fixed maximum strain, and the loading rate was 10mm / s. For specimens with prefabricated cracks, the loading process was recorded with a video recorder to obtain the relationship between the number of cycles and the crack extension length. The energy release rate is calculated as follows:

[0046] G=W(λ)×H,

[0047] Where W(λ) is the integral area of ​​the stress-strain curve of the notched specimen from 1 to the maximum strain λ of the Nth week. H is the initial gauge height of the specimen. If the fiber breaks, N is taken as the week before the break. If the fiber does not break and the crack stops, N is taken as the stress-strain curve under the 30,000th week of loading. The fatigue threshold value of the composite hydrogel presents two limits, one is the fatigue threshold value at which the crack does not extend at all, and the other is the fatigue threshold value at which the crack stops after the fiber takes effect.

[0048] Example 2: Preparation method of a low modulus anti-fatigue composite hydrogel

[0049] This embodiment provides an anti-fatigue polyvinyl alcohol hydrogel and a preparation method thereof, which differs from Example 1 only in that the mass fraction of the polyvinyl alcohol aqueous solution poured into the mold containing the fabric is 5%.

[0050] Example 3: Preparation method of a low modulus anti-fatigue composite hydrogel

[0051] This embodiment provides an anti-fatigue polyvinyl alcohol hydrogel and a preparation method thereof, which differs from Example 1 only in that the mass fraction of the polyvinyl alcohol aqueous solution poured into the mold containing the fabric is 20%.

[0052] Example 4: Preparation method of a low modulus anti-fatigue composite hydrogel

[0053] This embodiment provides an anti-fatigue polyvinyl alcohol hydrogel and a preparation method thereof, which differs from Example 1 only in that the annealing time in a 40°C constant temperature box is 24 hours.

[0054] Example 5: Preparation method of a low modulus anti-fatigue composite hydrogel

[0055] This embodiment provides an anti-fatigue polyvinyl alcohol hydrogel and a preparation method thereof, which differs from Example 1 only in that the annealing temperature in the thermostat is 110°C.

[0056] Example 6: A low modulus anti-fatigue composite hydrogel, preparation method and

[0057] First, a mold made of two glass plates and a layer of 0.5 mm hollow silicone was prepared; two pieces of 0.15 mm thick plain weave fabrics were soaked overnight in a mixed solution containing 90 wt% alcohol and 10 wt% acetone to remove the oil and wax on the surface of the fabrics. Then the fabrics were stacked at 90° and placed in the above mold ( Figure 2 Schematic diagram of the angle of laying of multi-layer fabrics). Then, a 10% polyvinyl alcohol aqueous solution was poured into the mold containing the fabric. The mixture and the mold were placed in a refrigerator and frozen at -20°C for 12 hours, followed by thawing at room temperature for 3 hours. Next, the composite hydrogel in the mold was removed and annealed in a 40°C thermostat for 2 hours. Finally, the annealed composite material was immersed in deionized water for 24 hours.

[0058] The composite hydrogel provided in Example 1 was subjected to tensile mechanical testing using an electronic universal testing machine. The strain-stress curve is shown in FIG. Figure 8 As shown by Figure 8 It can be seen that the composite hydrogel has a J-type stress-strain curve similar to that of biological tissue. The test conditions of the electronic universal testing machine are: at room temperature, the mechanical sensor is 100N, and the stretching speed is 50mm / min.

[0059] The fracture toughness test of the composite hydrogel provided in Example 1 was carried out using an electronic universal testing machine. The strain-stress curve thereof is shown in FIG. Fig. 9 As shown by Fig. 9 It can be seen that the fracture toughness of the composite hydrogel is 50 kJ / m 2. Among them, the test conditions of the electronic universal testing machine are: at room temperature, the mechanical sensor is 100N, and the tensile speed is 50mm / min. The method of fracture toughness test is: cut the test sample into a rectangle with a width of 50mm and a height of 30m. For specimens with prefabricated cracks, introduce a 20mm pre-crack in the middle plane. Fix the edge of the specimen on the acrylic plate to ensure that the gauge height is 10mm. Measure the thickness of each specimen with a micrometer screw before the test. According to the specimen with prefabricated cracks, the critical fracture tensile ratio λc is determined at the starting point of crack extension. The calculation method of fracture toughness G is as follows,

[0060] Γ=W(λc)×H,

[0061] Where W(λc) is the integral area of ​​the stress-strain curve of the notched specimen from 1 to the critical fracture tensile ratio. H is the initial gauge height of the specimen.

[0062] The fatigue resistance of the composite hydrogel provided in Example 1 was tested using an electronic universal testing machine. The test results are as follows: Fig.10 As shown by Fig.10 It can be seen that the fatigue threshold of the composite hydrogel is 5440J / m 2 . Among them, the test conditions of the electronic universal testing machine are: at room temperature, the mechanical sensor is 100N, and the tensile speed is 50mm / min. The method of fatigue threshold value test is: cut the test sample into a rectangle with a width of 50mm and a height of 30mm. For specimens with prefabricated cracks, introduce a 20mm pre-crack in the middle plane. Fix the edge of the specimen on the acrylic plate to ensure that the gauge height is 10mm. Measure the thickness of each specimen with a micrometer screw before the test. The specimen was immersed in a deionized water environment for testing. During the test, the unnotched specimens and the specimens with prefabricated cracks were subjected to cyclic loading with a fixed maximum strain, and the loading rate was 10mm / s. For specimens with prefabricated cracks, the loading process was recorded with a video recorder to obtain the relationship between the number of cycles and the crack extension length. The energy release rate is calculated as follows:

[0063] G=W(λ)×H,

[0064] Where W(λ) is the integral area of ​​the stress-strain curve of the notched specimen from 1 to the maximum strain λ of the Nth week. H is the initial gauge height of the specimen. If the fiber breaks, N is taken as the week before the break. If the fiber does not break and the crack stops, N is taken as the stress-strain curve under the 30,000th week of loading. The fatigue threshold value of the composite hydrogel presents two limits, one is the fatigue threshold value at which the crack does not extend at all, and the other is the fatigue threshold value at which the crack stops after the fiber takes effect.

[0065] Example 7: Preparation method of a low modulus anti-fatigue composite hydrogel

[0066] This embodiment provides an anti-fatigue polyvinyl alcohol hydrogel and a preparation method thereof. The only difference between this embodiment and embodiment 1 is that the number of fabrics laid in the mold is 12 layers, the laying angle is 30°, and other conditions are the same as those in embodiment 1.

[0067] Example 8: A method for preparing a low modulus fatigue-resistant composite hydrogel for in vitro fatigue testing of artificial heart valve prostheses.

[0068] The composite hydrogel was sutured to a stainless steel metal stent and obtained Fig.11 An artificial heart valve prosthesis is shown. Fig.12 This is a diagram of the opening and closing state of the composite hydrogel under pulsating flow. Its low modulus property makes the artificial heart valve prosthesis made of composite hydrogel have a good opening and closing shape. The artificial heart valve prosthesis composed of composite hydrogel and metal stent was installed on an accelerated wear tester and subjected to pulsating flow circulation at a frequency of 15Hz, and an in vitro high-cycle fatigue test was performed on it. The artificial heart valve prosthesis made of composite hydrogel remained intact even after 25,000,000 cycles. Fig.13 This is a scanning electron microscope photo after high-cycle fatigue testing. It can be found that the composite hydrogel did not show any cracks after ultra-high cycle loading, proving that the low-modulus fatigue-resistant composite hydrogel has the potential to be used in artificial heart valve prostheses.

[0069] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A low modulus anti-fatigue composite hydrogel, characterized in that: It comprises a hydrogel-based soft matrix layer and a reinforced knitted fabric layer covering the hydrogel-based soft matrix layer; the material of the hydrogel-based soft matrix layer is a low-modulus hydrogel; the material of the reinforced knitted fabric layer is a stretchable fabric woven from high-strength fibers with a curved fiber structure, which can form bridging fibers under cyclic loads to resist fatigue crack propagation.

2. A low modulus anti-fatigue composite hydrogel according to claim 1, characterized in that: The modulus of the hydrogel-based soft matrix layer is less than 1Mpa, and the stretch ratio is greater than 2; the strength of the reinforced knitted fabric layer is greater than 10MPa, and the gram weight is greater than 80g / cm 2 , the underfill coefficient is greater than 10; The soft matrix and knitted fabric form a strong interface, which makes the soft matrix and knitted fabric deform synergistically, effectively improving the fatigue resistance of the hydrogel. The fatigue threshold value of the composite hydrogel is greater than 5000J / m 2 At the same time, the initial modulus of the knitted fabric is low, so that the composite hydrogel maintains a low modulus of less than 1MPa.

3. The method for preparing a low modulus anti-fatigue composite hydrogel according to claim 1 or 2, characterized in that: The steps include: (1) Laying a single layer or multiple layers of stretchable fabric in a mold; (2) pouring a hydrogel precursor solution into the mold of step (1), subjecting the entire mold to a freeze-thaw cycle, and demolding the mold to form a prefabricated composite hydrogel; (3) placing the prefabricated composite hydrogel obtained in step (2) in an oven for annealing and drying to obtain an annealed composite hydrogel; (4) Immersing the annealed composite hydrogel obtained in step (3) in a solution until complete swelling equilibrium is reached; and obtaining a low modulus fatigue-resistant composite hydrogel.

4. The method for preparing a low modulus anti-fatigue composite hydrogel according to claim 3, characterized in that The mold described in step (1) includes two glass plates and a layer of hollow silicone pad, wherein the hollow silicone pad is located between the two glass plates.

5. The method for preparing a low modulus anti-fatigue composite hydrogel according to claim 3, characterized in that The fibers used for the stretchable fabric in step (1) include any one or more of metal, polyurethane, nylon, Kevlar, polyester, polytetrafluoroethylene, ultra-high molecular weight polyethylene, polyetheretherketone, polysulfone, polyether, polyamide, and polyetherimide; the stretchable fabric structure is any one or more of warp knitting or weft knitting plain needle structure, rib structure, double rib structure, and double-sided structure; the diameter of any fiber in the stretchable fabric in step (1) is 10 to 100 microns; the laying angle θ between the multiple layers of stretchable fabric laid in the mold in step (1) is 1-360°; the stretchable fabric can be pre-stretched and tensioned with a deformation of up to 200%.

6. The method for preparing a low modulus anti-fatigue composite hydrogel according to claim 3, characterized in that In step (2), the precursor in the hydrogel precursor solution includes any one or a combination of at least two of compounds such as polyvinyl alcohol, polyethylene glycol, acrylamide, acrylic acid, hyaluronic acid, cellulose, sodium alginate, chitosan, etc.; the solvent of the hydrogel precursor solution is any one or more of water, tetrahydrofuran, dimethyl sulfoxide, ethanol, and acetone; the mass percentage of the precursor in the precursor solution is 1 to 20%.

7. The method for preparing a low modulus anti-fatigue composite hydrogel according to claim 3, characterized in that The temperature of the cold source used in the freeze-thaw cycle in step (2) is -80 to -20°C; the freezing time is 6 to 24 hours.

8. A method for preparing a low modulus fatigue-resistant composite hydrogel as claimed in claim 3, characterized in that In step (3), the temperature of the annealing and drying is controlled at 30 to 110°C, and the temperature control time is 1 to 1440 minutes.

9. The method for preparing a low modulus anti-fatigue composite hydrogel according to claim 3, characterized in that In step (4), the swelling solution is any one of deionized water, dimethyl sulfoxide, ethanol, and ionic liquid, or a combination of at least two of them. The swelling time is 1 to 2880 minutes, and the temperature of the immersion in the solution is 0 to 80°C.

10. The use of a low modulus anti-fatigue composite hydrogel according to claim 1 or 2, characterized in that: The composite hydrogel is cut into artificial heart valve leaflets, sewn onto a metal stent, and assembled into an artificial heart valve prosthesis, which can open and close smoothly under the action of pulsating flow and withstand 25,000,000 cyclic loads without being damaged.

Citation Information

Patent Citations

  • Interventional cardiac valve prosthesis based on polymer fiber composite material and preparation method of interventional cardiac valve prosthesis

    CN108904877A

  • Nanofiber-hydrogel composites for enhanced soft tissue replacement and regeneration

    CN112423799A

  • Preparation method of long-term replacement type anti-fatigue meniscus

    CN116039113A

  • Flexible fabric / gel composite material and preparation method and application thereof

    CN116043548A

  • Hydrogel electrode with anti-fatigue bonding property as well as preparation method and application of hydrogel electrode

    CN116115781A